Handbook of Anticancer Drugs From Marine Origin 2014
DOI: 10.1007/978-3-319-07145-9_31
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer Effects of Triterpene Glycosides, Frondoside A and Cucumarioside A2-2 Isolated from Sea Cucumbers

Abstract: Very low toxicity and various in vitro effects of triterpene glycosides make it a suitable agent for cancer prevention and treatment. The molecular mechanisms of action of marine triterpene glycosides, including Frondoside A and Cucumariosides on the apoptosis of cancer cells are not fully investigated. Frondoside A from sea cucumber Cucumaria frondosa and Cucumariosides from Cucumaria japonica are pentaosides and the main structural difference between Frondoside A and Cucumarioside A 2 -2 is in the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The cytotoxic activity of sea cucumber glycosides against different cell types and cell lines, including HeLa and THP-1, has been extensively studied [1,19]. This has led to deeper understanding of the mechanisms of the anticancer activities of glycosides [7,8,20]. Different tumor cell lines exhibit different sensitivities to the cytotoxic effects of sea cucumber glycosides, depending on their chemical structures.…”
Section: Bioactivity Of the Glycosidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytotoxic activity of sea cucumber glycosides against different cell types and cell lines, including HeLa and THP-1, has been extensively studied [1,19]. This has led to deeper understanding of the mechanisms of the anticancer activities of glycosides [7,8,20]. Different tumor cell lines exhibit different sensitivities to the cytotoxic effects of sea cucumber glycosides, depending on their chemical structures.…”
Section: Bioactivity Of the Glycosidesmentioning
confidence: 99%
“…Recently, we published a paper concerning the isolation, structural elucidation, and biologic activity of a series of the glycosides, named chitonoidosides A-E, isolated from P. chitonoides [15]. These compounds feature some interesting structural features, such as a new, non-holostane aglycone lacking a lactone and featuring an 18 (20)-epoxy cycle, 3-O-methylxylose residue in the carbohydrate chains of three of them, the sulfation of 3-Omethylxylose by C-4, and, finally, a rather rare architecture of tetrasaccharide carbohydrate chain branched by C-4 Xyl1. As a continuation of our research on the glycosides from this species, four new chitonoidosides, E 1 (1), F (2), G (3), and H (4), are reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, they believe consumption of sea cucumbers enhances the immune system and possesses aphrodisiac properties. Thus, food supplements comprising sea cucumber extracts are currently utilized in the treatment of cancer patients in Korea, Japan, China and other countries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in recent review, the mechanisms of the anticancer effects of triterpene glycosides, frondoside A and cucumarioside A 2 -2, were summarized with specific emphasis on the apoptotic activity of the glycosides and its effect on metastasis and invasion of cancer cells [ 58 ]. The authors concluded that these glycosides may be considered to be both anticancer and cancer preventive agents.…”
Section: Anticancer Activitymentioning
confidence: 99%